LITERATURE REVIEW: PENERAPAN BIG DATA DALAM KESEHATAN MASYARAKAT - Widya Sulaiman, Thirsya; Bagas Fitriansyah, Raka; Rafif Alaudin, Ahmad; Ratsanjani, M. Hasyim (Lafadz Jaya Publisher, 2023)
This research is conducted to determine the correlation and implementation of big data towards public health, which can then become a solution in Indonesia that is currently facing the triple burden. This study will review previous literature to find and gather information that can fulfill the research objectives. The results of this research show that big data combined with other disciplines such as AI, IoT, and machine learning have their own benefits and challenges. The challenges include data privacy, accuracy of results, and validation of information spread. On the other hand, the benefits are used to assist in public service activities and government in achieving goals and solving problems regarding public health, through disease surveillance and signal detection, predicting public health risks leading to opportunities to implement prevention interventions, identifying and understanding more about diseases, developing more accurate drugs, and providing more precise care with existing drugs.